Fabrication of TiO2-strontium loaded CaSiO3/ biopolymer coatings with enhanced biocompatibility and corrosion resistance by controlled release of minerals for improved orthopedic applications. (July 2016) - Raj, V.; Raj, R. Mohan; Sasireka, A.; Priya, P.
Abstract: Titanium dioxide (TiO2 ) arrays were fabricated on Ti alloy by anodization method. Synthesis of CaSiO3 (CS) and various concentrations (1X-5X) of Sr 2+ substitutions in CS coatings on TiO2 substrate was achieved through an electrophoretic deposition technique. Fast release of mineral ions from implant surface produce over dosage effect and it is a potential hazardous factor for osteoblasts. So, in order to prevent the fast release of minerals, biopolymer coating was applied above the composite coatings. The coatings were characterized by FTIR, XRD, FE-SEM and EDX techniques. The mechanical, anticorrosion, antimicrobial properties and biocompatibility of the coatings were evaluated. Studies on the mechanical properties indicate that the addition of Sr 2+ and biopolymer increase the hardness strength of the coatings. The metal ion release from the coatings was studied by ICP-AES. The electrochemical properties of the coatings were studied in Ringer's solution, in which CS-3X/Chi-PVP coating on TiO2 exhibits good anticorrosion property and high resistivity against Escherichia coli and Staphylococcus aureus compared to CS-3X coating on TiO2 . In vitro cell experiments indicate that osteoblasts show good adhesion and high growth rates for CS-3X/Chi-PVP coated TiO2 substrate, indicating that the surface cytocompatibility of CS-3X/Chi-PVP coated TiO2 substrate is significantly improved by the controlled release of mineral ions. In conclusion, the surface modification of TiO2 /CS-3X/Chi-PVP coated titanium is a potential candidate for implant coating. Graphical abstract: